Laparoscopic colposuspension to the Cooper's ligament after hysterectomy for uterovaginal prolapse. Issue 3 (20th November 2012) - Yoon, Won Sik; Lee, Hae Nam; Lee, Yong Seok; Jeung, In Cheul; Park, Eun Kyung
Abstract Aim The goal of this study was to evaluate the long‐term outcomes of laparoscopic colposuspension to the Cooper's ligament after hysterectomy for uterovaginal prolapse. Material and Methods We performed chart reviews of 43 patients with uterovaginal prolapse who underwent laparoscopic colposuspension to the Cooper's ligament after hysterectomy at Daejeon St. Mary's Hospital, Catholic University of Korea from 2003 to 2009. These patients exhibited grade 3 (29 patients) or grade 4 (14 patients) uterovaginal prolapse. Results The mean age was 63.2 years (range, 39–76). The mean follow‐up period was 44.2 months (95% CI, 36.8–51.5). Forty‐three patients showed no sign or recurrence of prolapse. Postoperative complications were tolerable and curable. Urinary frequency (2 patients, 4.7%), voiding difficulty (2 patients, 4.7%), nocturia (1 patient, 2.3%) and vaginal spotting (1 patient, 2.3%) were reported. Conclusion Laparoscopic colposuspension using Cooper's ligament after hysterectomy could be an effective surgical option for the treatment of uterovaginal prolapse.